Keunggulan Kompetitif Kelompok Pedagang Sektor Informal Pendatang - Slamet Santoso (ARISTO, 2018)
This study aims to to understand and illustrating the effort to encourage school a competitive advantage well as to the vendors angkringan order to be able to maintain a venture thus being able to compete in the city of ponorogo. Was used in the study a qualitative approach was adopted by applying a technique purposive the sampling method of as the determination of the subject matter of the research. The technique of an excavation data using in depth interviews and observation. While the technique of of the data analysis use the model interactive. The research results show that 1). a group of traders both jews and the proselytes angkringan in the city of ponorogo it is able to defend and develop their business; 2). their ability in of maintaining and developing its business caused by existence of the superiority and dominion of maintained the company competitiveness in government in their efforts to arab nations as a bloc; 3). a competitive edge of which there are applied with the value of the belief or joined as regards allah religion will try to get away and value of please the power to do anything help each other out local community and is developing in the group historically traders angkringan; and 4). the value of the community’s trust and the value of help one another are not limited to financial problems or business capital, but in the form of information important about business opportunities, help residence, and scouted for permission to occupy a location strategic to venture angkringan in the city ponorogo.